Analyzing The Performance Properties Of Stress Absorbing Membrane Interlayer Modified With Recycled Crumb Rubber - Asgharzadeh, Seyed Mohammad; Moein Biglari (Zenodo, 2017)
Asphalt overlay is the most commonly used technique of pavement rehabilitation. However, the reflective cracks which occur on the overlay surface after a short period of time are the most important distresses threatening the durability of new overlays. Stress Absorbing Membrane Interlayers (SAMIs) are used to postpone the reflective cracking in the overlays. Sand asphalt mixtures, in unmodified or crumb rubber modified (CRM) conditions, can be used as an SAMI material. In this research, the performance properties of different SAMI applications were evaluated in the laboratory using an Indirect Tensile (IDT) fracture energy. The IDT fracture energy of sand asphalt samples was also evaluated and then compared to that of the regular dense graded asphalt used as an overlay. Texas boiling water and modified Lottman tests were also conducted to evaluate the moisture susceptibility of sand asphalt mixtures. The test results showed that sand asphalt mixtures can stand higher levels of energy before cracking, and this is even more pronounced for the CRM sand mix. Sand asphalt mixture using CRM binder was also shown to be more resistance to moisture induced distresses. : {"references": ["Mallik, R. and T. El-Korchi, Pavement Engineering: Principles and Practice-Chapter 5. 2009, Taylor & Francis Group, Boca Raton, USA, ISBN987\u20131\u20134200\u20136029\u20134.", "Shalaby, A. and L. Fr\u00e9chette. Reflective cracking on C-SHRP long term pavement performance sites. in Reflective Cracking In Pavements-Research In Practice. Proceedings Of The 4th International Rilem Conference, 26-30 March 2000, Ottawa, Canada. 2000.", "Caltabiano, M. and J. Brunton, Reflection Cracking In Asphalt Overlays (With Discussion). Journal of the Association of Asphalt Paving Technologists, 1991. 60.", "Dhakal, N., M.A. Elseifi, and Z. Zhang, Mitigation strategies for reflection cracking in rehabilitated pavements\u2013A synthesis. International Journal of Pavement Research and Technology, 2016. 9(3): p. 228-239.", "Penman, J. and K. Hook. The use of geogrids to retard reflective cracking on airport runways, taxiways and aprons. in RILEM International Conference on Cracking in Pavements (6th: 2008: Chicago, Ill.). 2008.", "Molenaar, A., J. Heerkens, and J. Verhoeven. Effects of stress absorbing membrane interlayers. in Association of Asphalt Paving Technologists Proc. 1986.", "West, R., et al., Effect of tire rubber grinding method on asphalt-rubber binder characteristics. Transportation Research Record: Journal of the Transportation Research Board, 1998(1638): p. 134-140.", "J. A. Cooper, D. F. L. a. R. C. A., Stress Absorbing Membrane Interlayer(S.A.M.I.). Materials Information Report 50, 1983.", "Yang, J., et al. Asphalt sand stress absorbing interlayer used in asphalt pavement with semi-rigid base. in 6TH RILEM International Conference on Cracking in Pavement. 2008.\n[10]\tBaek, J. and I. Al-Qadi, Sand mix interlayer to control reflective cracking in hot-mix asphalt overlay. Transportation Research Record: Journal of the Transportation Research Board, 2011(2227): p. 53-60.\n[11]\tMoses, O., Mechanical behaviour of stress absorbing membrane interlayers. Civil Engineering Department. PhD Thesis, University of Nottingham, Nottingham, United Kingdom, 2011.\n[12]\tAmirkhanian, S.N., F. Xiao, and K. Sockwell. Performance Properties of Polymer Modified Pelletized Asphalt Mixtures. in Airfield and Highway Pavements 2015. 2015.\n[13]\tXiao, F., S. Amirkhanian, and C. H. Juang, Rutting resistance of rubberized asphalt concrete pavements containing reclaimed asphalt pavement mixtures. Journal of Materials in Civil Engineering, 2007. 19(6): p. 475-483.\n[14]\tPutman, B.J. and S.N. Amirkhanian. Crumb rubber modification of binders: interaction and particle effects. in Proceedings of the Asphalt Rubber 2006 Conference. 2006.\n[15]\tNejad, F. M., et al., Investigating the properties of crumb rubber modified bitumen using classic and SHRP testing methods. Construction and Building Materials, 2012. 26(1): p. 481-489.\n[16]\tWang, H., et al., Analysis on fatigue crack growth laws for crumb rubber modified (CRM) asphalt mixture. Construction and Building Materials, 2013. 47: p. 1342-1349.\n[17]\tHicks, R.G. and J.A. Epps, Quality control for asphalt rubber binders and mixes. Proceedings, Asphalt Rubber, 2000: p. 13-17.\n[18]\tDau\u010d\u00edk, P., Hadvinov\u00e1, M., Vi\u0161\u0148ovsk\u00fd, J. (2011). Methods For Determination Of Affinity Between Aggregate and Bitumen, 45th International Petroleum Conference, Bratislava, Slovak Republic.\n[19]\tMaupin, G., Installation and early performance of a field test section of asphalt rubber concrete. 1991.\n[20]\tBahadori, A., A. Mansourkhaki, and M. Ameri, A Phenomenological Fatigue Performance Model of Asphalt Mixtures Based on Fracture Energy Density. Journal of Testing and Evaluation, 2014. 43(1): p. 133-139.\n[21]\tHasan, Z., et al., Long term performance of warm mix asphalt versus hot mix asphalt. Journal of Central South University, 2013. 20(1): p. 256-266.\n[22]\tMehrara, A. and A. Khodaii, A review of state of the art on stripping phenomenon in asphalt concrete. Construction and Building Materials, 2013. 38: p. 423-442.\n[23]\tTarefder, R.A. and A.M. Zaman, Nanoscale evaluation of moisture damage in polymer modified asphalts. Journal of Materials in Civil Engineering, 2009. 22(7): p. 714-725.\n[24]\tOtsu, N., A threshold selection method from gray-level histograms. IEEE transactions on systems, man, and cybernetics, 1979. 9(1): p. 62-66.\n[25]\tAnderton, G. L., et al., Construction Productivity Advancement Research (CPAR) Program. 1992, DTIC Document."]}